Minerva: An Adaptive and Personalized Solution for Organizing Studies Based on Learning Cycles - Sousa, Imna P. N. de; Farias, Luan Mateus S.; Sousa, Gustavo Henrique L.; Andrade, Rossana Maria de Castro; Oliveira, Pedro Almir Martins de (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2025)
This paper presents Minerva, a mobile application designed to help students organize their study routines through adaptive and personalized learning cycles. Grounded in principles such as meta-cognition, spaced repetition, and self-regulated learning, Minerva offers features like a habit tracker, learning trail, progress dashboard, and intelligent scheduling. Unlike traditional study methods, the application enables users to dynamically adjust study goals based on personal performance and availability, promoting autonomy and motivation. An exploratory study involving 50 students was conducted based on the UTAUT model. The results indicate a high level of acceptance of the app’s concept, particularly among students with no prior experience using similar tools. Participants emphasized its innovation, usefulness, and potential impact on their study habits. While still under development, the proposal demonstrates its potential to the scientific community by integrating evidence-based educational theories with user-centered design practices. This study contributes to the advancement of adaptive educational technologies. It opens up discussions for future investigations into the efficacy of learning cycle-based study tools.